New Routes in GPCR/β-Arrestin-Driven Signaling in Cancer Progression and Metastasis - Bagnato, Anna; Rosanò, Laura (Frontiers in Pharmacology, 2019)
Tumor cells acquire invasive and metastatic behaviour by sensing changes in the localization and activation of signalling pathways, which in turn determine changes in actin cytoskeleton. The core-scaffold machinery associated to β-arrestin (β-arr) is a key mechanism of G-protein coupled receptors (GPCR) to achieve spatiotemporal specificity of different signalling complexes driving cancer progression. Within different cellular contexts, the scaffold proteins β-arr1 or β-arr2 may now be considered organizers of protein interaction networks involved in tumor development and metastatic dissemination. Studies have uncovered the importance of the β-arr engagement with a growing number of receptors, signalling molecules, cytoskeleton regulators, epigenetic modifiers and transcription factors, in GPCR-driven tumor promoting pathways. In many of these molecular complexes, β-arrs might provide a physical link to active dynamic cytoskeleton, permitting cancer cells to adapt and modify the tumor microenvironment to promote the metastatic spread. Given the complexity and the multidirectional β-arr-driven signalling in cancer cells, therapeutic targeting of specific GPCR/β-arr molecular mechanisms is an important avenue to explore when considers future new therapeutic options. The focus of this review is to integrate the most recent developments and exciting findings of how highly connected components of β-arr-guided molecular connections to other pathways allow precise control over multiple signalling pathways in tumor progression, revealing ways of therapeutically targeting the convergent signals in patients.